POLA KOMUNIKASI RESES ANGGOTA DPRD KOTA MAKASSAR DALAM MENYERAP ASPIRASI MASYARAKAT (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research is focused on two main problems, namely: 1). how is the communication pattern of the Makassar City DPRD members' recess in absorbing the aspirations of the community? 2). What factors support and hinder the communication pattern of DPRD members' recess in absorbing people's aspirations? This study uses a qualitative research type and is located at the Makassar City DPRD Secretariat Office. The research approach used is the study of communication science with a concentration on communication patterns. In this study, data were compiled and collected from various sources, such as interviews, documentation, and also observations at the research site. This study also describes an event, an event that occurs through data collection methods and is also field in nature. The results of this study indicate that 1) the communication pattern of the Makassar City DPRD recess in absorbing the aspirations of the community is measured through several indicators of the communication process involving elements of communication, namely communicators, communicants, messages, media, and feedback. From these recess processes, it was found that in the preparation of the recess, the communication pattern used was a top-down communication pattern, namely from the leadership of the DPRD to DPRD members, then in the implementation of the recess it was found that top-down communication patterns were found from DPRD members to the community and bottom-up communication patterns from the community to members. The DPRD, in following up on the results of the recess, found a horizontal communication pattern, namely DPRD members and the Makassar City Government. Furthermore, from the overall data obtained the wheel pattern on the recess communication pattern of DPRD members in absorbing community aspirations, 2) Factors that support the recess communication pattern, namely the community and the Makassar City DPRD secretariat greatly assist the process of recess activities for DPRD members in carrying out their functions and duties so that the desired goals can be achieved. achieved. The inhibiting factors in the recess communication pattern are the busyness of DPRD members in attending recess activities which can hinder activities as well as other inhibiting factors regarding time constraints, and budget constraints so that people's aspirations are not immediately realized.